INFERENSI FUNGSI KETAHANAN DENGAN METODE KAPLAN-MEIER - Widiharih, Tatik; Andriani, Nasichah Siska (MATEMATIKA, 2006)
. Let T be a nonnegatif random variable representing the life time of individuals in some population. Life time data of individuals are devided in two kinds, cencored and uncencored data. The probability of an individual surviving till time t is given by the survival function S(t)=P(Tâ‰¥t). Product Limit estimator (Kaplan-Meier estimator) is a nonparametric method to find the survival function for cencored data. Â